Health Professionals Should be Involved in Shaping Substance Use Disorder Policy. Issue 4 (July 2020) - Rosenbloom, David L.; Lewis, David C.
Abstract : N/A: Health professionals should become actively involved in creating evidence based SUD policies as individuals; as members of advisory commissions; as advocates within professional associations and through participation in political campaigns as candidates, donors or activists.